Practical problems in mathematics for automotive technicians - Sformo, Todd (Delmar's practical problems in mathematics series, 2004)
Organised in a knowledge-building format that progresses from the basics of whole number operations to percentages, linear measurements, ratios and the use of more complex formulas makes this book suitable for both beginning and advanced technicians.